Pengaruh Kreativitas dan Inovasi Terhadap Kinerja Usaha UKM Tenun Motif Renda Kota Bima - Efendi Febriansyah; . Muhajirin (Jurnal Ekonomi Manajemen Perbankan, 2020)
The purpose of this study was to determine the effect of creativity and innovation on the business performance of Bima City Lace Motifs in partially or simultaneously. The type of research used is associative, the research location is Raba Subdistrict, Ntobo Village. The population in this study are all UKM Lace motif that have Creativity and Innovation, the sample in this study amounted to 100 UKM.  The research instrument used a questionnaire with a Likert scale measurement The type of data used in this study was quantitative data and the source of research data was primary data. Data collection techniques are observation, questionnaire / questionnaire, and literature study. The Creativity and Innovation Variables together have an effect both simultaneously and partially and simultaneously on the Business Performance of Bima City Lace Motifs. The implication of this research is that the existence of lace motif products can continue to be recognized and developed in order to preserve the Bima City lace motif woven products.